2020
DOI: 10.24198/pjd.vol32no2.23917
|View full text |Cite
|
Sign up to set email alerts
|

Association of rs235768 A>T polymorphism of the bone morphogenetic protein 2 gene on non-syndromic orofacial cleft in an Indonesian population

Abstract: Introduction: Orofacial cleft is one of the many congenital malformations that often occur in human, leaving it at the fourth level of the most common orofacial birth defect findings. The incident rate is one in 700-1000 deliveries, where without therapeutic and surgical interventions, children with an orofacial cleft may have problems with speech, nutrition intake, and growth. Bone morphogenetic protein 2 (BMP-2) gene play essential roles in the migration and proliferation of neural crest cell of the early he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Recently, a study on BMP2 (rs235768) has reported that the missense BMP2 variant (Argenine > Serine) is involved in decreased mandibular length and craniofacial development including tooth agenesis ( Küchler et al, 2021 ). Other studies reported an association between the BMP2 rs235768 with orofacial cleft ( Kiranahayu et al, 2020 ). Our data identified the same association between BMP2 rs235768 and mandibular retrognathism, decreased anterior facial height (hyodivergent face), decreased mandibular, and increased maxillary anterio-posterior length.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, a study on BMP2 (rs235768) has reported that the missense BMP2 variant (Argenine > Serine) is involved in decreased mandibular length and craniofacial development including tooth agenesis ( Küchler et al, 2021 ). Other studies reported an association between the BMP2 rs235768 with orofacial cleft ( Kiranahayu et al, 2020 ). Our data identified the same association between BMP2 rs235768 and mandibular retrognathism, decreased anterior facial height (hyodivergent face), decreased mandibular, and increased maxillary anterio-posterior length.…”
Section: Discussionmentioning
confidence: 97%